Effects of temperature on the life-history traits of Myzus persicae and its efficiency in transmitting potato virus Y (PVY) in potato crops - Sokame, B.M.; Tonnang, H.E.; Gamarra, H.; Carhuapoma, Pablo; Kreuze, Jan F.; Arab, A.; Armbruster, P.A.; Johnson, L.R.; Villena, O.C. (2024)
Aphids are highly sensitive to temperature changes and play a crucial role in transmitting plant viruses, accounting for the transmission of more than 50% of viruses that cause disease in crops. Among them, Myzus persicae is a major global pest, affecting over 400 plant species and transmitting more than 100 plant viruses, including potato virus Y (PVY), which poses a severe threat to potato crops. This study examines how temperature influences the life-history traits of M. persicae and its efficiency in transmitting PVY. Our research revealed that temperature significantly affects developmental duration, survival, and fecundity of M. persicae. The aphids exhibit the longest lifespan at 10°C and the shortest at 30°C. Similarly, fecundity declined from 29.81 offspring per female at 10°C to 14.25 at 30°C. PVY transmission efficiency was highest at 20°C. We also mapped potential PVY transmission regions and identified tropical and subtropical areas as high-risk due to their favourable temperatures and aphid’s abundance. Understanding these geographical variations is crucial for effective pest/disease management. Our findings emphasize the importance of integrating climatological, ecological, and epidemiological data to develop robust pest/disease management strategies to mitigate the impact of M. persicae and PVY on potato production and enhancing global food security.